"If You Love Me, You Must Do..." Parental Psychological Control and Cyberbullying Perpetration Among Chinese Adolescents. Issue 9 (May 2022) - Geng, Jingyu; Wang, Xingchao; Wang, Yuhui; Lei, Li; Wang, Pengcheng
Considering the prevalence of cyberbullying, the current study explores the factors associated with its perpetration. Using self-determination theory, the association of parental psychological control (PPC) with cyberbullying perpetration was examined. To explore this influencing mechanism further, psychological reactance (PRt) and materialism were examined as two mediators in this relationship. Moreover, according to the diathesis–stress model and cognitive model of resilience, psychological resilience (PRl) was examined as a moderator in the direct and indirect link between PPC and cyberbullying perpetration. To test our expectations, 804 adolescents ( M = 13.12, SD = 1.16) participated in the current study using a cross-sectional design and multiple questionnaires, namely, the Chinese version of the Parental Control Questionnaire, Revised Cyber Bullying Inventory, Hong Psychological Reactance Scale, Material Values Scale for Children, and Resilience Scale for Chinese Adolescents. Correlation analysis indicated that PPC, PRt, materialism, and cyberbullying perpetration were significantly and positively correlated, and were significantly and negatively related to PRl. Moderated mediation analysis revealed that PRt and materialism played multiple mediating roles in the relationship between PPC and cyberbullying perpetration. Multiple mediation analysis indicated that PRl weakened the direct associations of PPC, PRt, and materialism with cyberbullying perpetration, further alleviating the indirect and direct associations of PPC with cyberbullying perpetration, supporting the moderated mediation model. Specifically, adolescents high in PPC were more likely to have stronger PRt and materialistic values, which further triggered cyberbullying perpetration. PRl can protect adolescents high in PPC from cyberbullying perpetration via weakening the direct and indirect associations of PPC with cyberbullying.